Kajian Produksi Dan Analisis Mutu Pangan Tradisional Sere Kedele Di Kabupaten Klungkung, Bali - Irdayanti, Putri; Suparthana, I Putu; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPA, 2023)
Sere kedele is a traditional fermented soybean product. This type of food is processed by home industries, especially in Klungkung Regency and several areas in Gianyar. This research was conducted to obtain information related to the traditional production process and analysis of the quality of sere kedele, especially in the Klungkung Regency, Bali. This research carried out in two stages, namely a survei to determine the production process, raw/additional materials used, presentation method, production area, and distribution of sere kedele in Klungkung Regency. The second stage is to analyze the chemical properties of traditional sere kedele food in Klungkung Regency. The survei results show that there are five producers of sere kedele in the villages of Tusan, Tihingan, Galiran, Tojan, Akah and Besang. The processing of sere kedele is different for each producer, such as the length of boiling, the length of fermentation, and the stage of adding seasonings. The samples used in this study is raw sere kedele and fried sere kedele. Sere kedele mentah in Klungkung Regency contains water content 56.85%-60.85%, ash content 1.21%-1.34%, protein content 14.68%-22.04%, fat content 5.69%-9.62%, and carbohydrate content of 13.64%-15.16%. Meanwhile, fried soybean sere has a water content of 1.42%-4.46%, an ash content of 1.45%-1.83%, a protein content of 13.45%-30.65%, fat content of 36.14%-42,1%, and carbohydrate content is 26.78% -41.49%. Keywords: sere kedele, Klungkung, fermentation, traditional food